Beyond Structure: Using the Rational Force Model to Assess Argumentative Writing. (April 2023) - Backman, Ylva; Reznitskaya, Alina; Gardelli, Viktor; Wilkinson, Ian A. G.
Current approaches used in educational research and practice to evaluate the quality of written arguments often rely on structural analysis. In such assessments, credit is awarded for the presence of structural elements of an argument, such as claims, evidence, and rebuttals. In this article, we discuss limitations of such approaches, including the absence of criteria for evaluating the quality of the argument elements. We then present an alternative framework, based on the Rational Force Model (RFM), which originated from the work of a Nordic philosopher Næss. Using an example of an argumentative essay, we demonstrate the potential of the RFM to improve argument analysis by focusing on the acceptability and relevance of argument elements, two criteria widely considered to be fundamental markers of argument strength. We outline possibilities and challenges with using the RFM in educational contexts and conclude by proposing directions for future research.